2009
DOI: 10.1159/000231975
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Adiponectin Level in Patients with <i>Mycobacterium avium-intracellulare</i> Complex Pulmonary Disease

Abstract: Background: Patients with Mycobacterium avium-intracellulare complex (MAC) pulmonary disease often suffer from weight loss. Adipokines are factors secreted by adipocytes, including leptin and adiponectin, as well as some inflammatory cytokines, tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6). Body mass index (BMI) is known to be inversely correlated with adiponectin and positively with leptin, TNF-α, and IL-6. Objective: We aimed to evaluate the levels of serum adipokines, including adiponectin, lepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…The typically inverse relationship between body fat and adiponectin was absent in the patients with pNTM ( Figure 1B). Our findings do not replicate the work of Tasaka and colleagues (24), who showed that although adiponectin was elevated and leptin was reduced in patients with pNTM, there was no difference in the slopes of the linear regression lines between the groups. This may be due to the fact that they found no difference in BMI between the two cohorts.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The typically inverse relationship between body fat and adiponectin was absent in the patients with pNTM ( Figure 1B). Our findings do not replicate the work of Tasaka and colleagues (24), who showed that although adiponectin was elevated and leptin was reduced in patients with pNTM, there was no difference in the slopes of the linear regression lines between the groups. This may be due to the fact that they found no difference in BMI between the two cohorts.…”
Section: Discussioncontrasting
confidence: 99%
“…Reduced leptin levels in slender individuals may contribute to the increased susceptibility to TB (22,23). Tasaka and colleagues (24) found that patients with pNTM had 30% lower serum leptin as compared with healthy control subjects matched for age, gender, and BMI (24). Mouse studies show that leptin is a host-protective factor against M. tuberculosis and M. abscessus (25,26).…”
mentioning
confidence: 99%
“…Adipocyte-derived adipokines and related inflammatory cytokines have been suggested to contribute to increased susceptibility to PNTM disease (26). Tasaka et al reported elevated adiponectin levels and reduced leptin levels in patients with PNTM disease compared with healthy controls (27). Leptin deficiency results in impaired innate and adaptive immune functions.…”
Section: Discussionmentioning
confidence: 99%
“…Nontuberculous mycobacterial disease is one of the infectious granulomatous diseases in the lung [2,3,4,5]. It is characterized by the formation of various degrees of granulomas.…”
Section: Introductionmentioning
confidence: 99%